2000
DOI: 10.1136/ard.59.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in systemic lupus erythematosus: comparison with rheumatoid arthritis and healthy controls

Abstract: Objectives-To examine bone mineral density (BMD) frequency of osteoporosis and reduced bone mass in systemic lupus erythematosus (SLE), and compare the data of the SLE patients with matched rheumatoid arthritis (RA) patients and healthy controls. Secondly, to study possible correlations between BMD, demographic and disease variables in the SLE patients. Methods-Measures of BMD assessed by dual energy x ray absorptiometry were obtained from 75 SLE patients aged < 70 years, 75 RA patients matched for age, sex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
97
0
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 33 publications
14
97
0
9
Order By: Relevance
“…2055 (4)(5)(6)10,38). Two previous studies of childhood-onset SLE (12,13) also found lower BMD in the spine and femoral neck of patients compared with controls.…”
Section: Osteopenia In Patients With Childhood-onset Slementioning
confidence: 84%
“…2055 (4)(5)(6)10,38). Two previous studies of childhood-onset SLE (12,13) also found lower BMD in the spine and femoral neck of patients compared with controls.…”
Section: Osteopenia In Patients With Childhood-onset Slementioning
confidence: 84%
“…HRQoL is an important complement to measures of disease activity and damage (11)(12)(13). For instance, comparative studies have shown that patients with SLE 5 perceive reduced HRQoL compared with controls and in parity with several other diseases (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Økt forekomst av osteoporose er også påvist hos pasienter med andre inflammatoriske sykdommer som f.eks. SLE og ankyloserende spondylitt (33)(34)(35).…”
Section: Prevalens Av Osteoporoseunclassified